Saliva buatan meningkatkan kekuatan tekan semen ionomer kaca tipe II yang direndam dalam minuman isotonik (Artificial saliva increases the compressive strength of glass ionomer cement type II soaked in isotonic drinks) - Juliatri Juliatri; D.H.C. Pangemanan; Dwi Cahya Fitriyana (DiscoverSys Inc., 2014)
Immersion of glass ionomer cement (GIC) type II in acid drink like isotonic drink could reduce its compressive strength.This is due to the matrix degradation process of GIC in acid condition. However, there is artificial saliva that canneutralize this condition. The purpose of this study was to evaluate the effect of artificial saliva on compressive strengthof glass ionomer cement type II immersed in isotonic drink. The GICspecimens of 6 x 6 x 12 mm3beam were immersed for24 hours in distilled water, 24 hours in isotonic drink, 24 hours in isotonic drink continued with 72 hours in artificial saliva,48 hours in isotonic drink, and 48 hours in isotonic drink continued with 144 hours in artificial saliva. The compressivestrength was measured using Universal Testing Machine with a crosshead speed of 0.5 mm/min. Statistical analysis wasperformed by one-way ANOVA and post-hoc LSD test (=0.05) showed a significant difference of compressive strength(p<0,05). It was concluded that artificial saliva increases the compressive strength of GIC immersed in isotonic drink.